Process Modeling In Cold Forging Considering The Process-Tool-Machine Interactions - Kroiss, Thomas; Engel, Ulf; Merklein, Marion (Proc. of the 10th Int. Conf. on Numerical Methods in Industrial Forming Processes; AIP Conference Proceedings 1252, 2010)
In this paper, a methodic approach is presented for the determination and modeling of the axial deflection characteristic for the whole system of stroke-controlled press and tooling system. This is realized by a combination of experiment and FE simulation. The press characteristic is uniquely measured in experiment. The tooling system characteristic is determined in FE simulation to avoid experimental investigations on various tooling systems. The stiffnesses of press and tooling system are combined to a substitute stiffness that is integrated into the FE process simulation as a spring element. Non-linear initial effects of the press are modeled with a constant shift factor. The approach was applied to a full forward extrusion process on a press with C-frame. A comparison between experiments and results of the integrated FE simulation model showed a high accuracy of the FE model. The simulation model with integrated deflection characteristic represents the entire process behavior and can be used for the calculation of a mathematical process model based on variant simulations and response surfaces. In a subsequent optimization step, an adjusted process and tool design can be determined, that compensates the influence of the deflections on the workpiece dimensions leading to high workpiece accuracy. Using knowledge on the process behavior, the required number of variant simulations was reduced. © 2010 American Institute of Physics.
LFT Import::2019-08-05 (499)
Keywords: Cold Forging; Press Deflection; Process Modeling; Process-Tool-Machine Interactions